2013
DOI: 10.7314/apjcp.2013.14.4.2495
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat and Physical Activity in Relation to Breast Cancer among Polish Women

Abstract: Background: Dietary fat has been inconsistently associated with the risk of breast cancer. The purpose of this study was to examine the relationship between meat and animal and plant fat intake and breast cancer risk in subgroups by total lifetime physical activity, using data from a case-control study conducted in the Region of Western Pomerania, Poland. Materials and Methods: The study included 858 women with histological confirmed breast cancer and 1,085 controls, free of any cancer diagnosis. The study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 58 publications
1
32
0
1
Order By: Relevance
“…Also, there is a positive relationship between diabetes and obesity. Since other studies showed that overweigh and obesity are risk factors of BC (Helyer, 2010;Alegre, 2013;Kruk, 2013), so these results must be interpreted with caution, because this correlation might be happen by positive confounding of obesity.…”
Section: Discussionmentioning
confidence: 89%
“…Also, there is a positive relationship between diabetes and obesity. Since other studies showed that overweigh and obesity are risk factors of BC (Helyer, 2010;Alegre, 2013;Kruk, 2013), so these results must be interpreted with caution, because this correlation might be happen by positive confounding of obesity.…”
Section: Discussionmentioning
confidence: 89%
“…In the past decade, dietary carbohydrate, fiber and sugar has gained much attention in relation towards breast cancer risk according to menopausal status, but studies have been limited in developed countries (Cho et al, 2003;Holmes et al, 2004;Romieu et al, 2004;Mattisson et al, 2004;Nielsen et al, 2005;Giles et al, 2006;Cade et al, 2007;Lajous et al, 2008;Suzuki et al, 2008;Larsson et al, 2009;Wen et al, 2009;Park et al, 2009;Shikany et al, 2011;Zaineddin et al, 2012;Ferrari et al, 2013;Li et al, 2013;Woo et al, 2013). A few studies have appeared from South-East Asia and Eastern Europe (Kruk and Marchlewicz, 2013;Sangrajrang et al, 2013). Rice, bread, noodles, traditional snacks (kuih), tubers, various tropical fruits and green leafy vegetables are rich sources of dietary carbohydrate, fiber, sugar and have been the staple diet among Asian population specifically in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Cancers occurring as a result of viral infections such as Hepatitis B Virus (HBV), Hepatitis C Virus, and HPV are responsible for many deaths in the low and middle-income countries (Danaei, 2005). In the Middle East countries, particularly in the middle and high-income countries, the incidence of cancer has increased substantially as behavioral risk factors such as smoking, unhealthy diet, physical inactivity and obesity in both adults and children have increased (Rahim et al, 2014;Kruk and Marchlewicz, 2013;Qin, 2013). The incidence of cancer can be reduced by primary prevention through adopting a healthy lifestyle and environmental interventions (Danaei, 2005;Luqman et al, 2014).…”
Section: Awareness Of Risk Factors For Cancer Among Omani Adults-a Comentioning
confidence: 99%